Integrating Petrophysical Analysis and Seismic Interpretation for Oil and Gas Reserves Estimation in “TAU” Field, Jatibarang Sub–Basin, North West Java Basin - Ilham Nur E.N. Iskandar; Rian Cahya Rohmana; Widi Atmoko; Sally Ulianda Azalia; Jehezkiel Nafael Makapuan (Journal of Earth Energy Science, Engineering, and Technology, 2023)
The focus of the study is the North West Java Basin, specifically the Jatibarang Sub Basin within it. The research aims to identify new potential areas for hydrocarbon reserves using seismic interpretation, and tetrophysical analysis, also calculate the volume of reserves in those areas. According to the study, 2 potential areas for hydrocarbon reserves were identified in the Parigi Formation, 2 were identified in the Baturaja Formation, 3 were identified in the Talang Akar Formation, and 1 was identified in the Jatibarang Formation. No new potential areas were discovered in the Cibulakan Formation. The study used petrophysical interpretation of six wells to determine the average values of shale volume (9.57% to 29.87%), effective porosity (19.45% to 21.67%), and water saturation (69.73% to 93.50%) for each potential zone. The TAU-5 well in the Baturaja Formation (Zone 1, Zone 2, Zone 3, and Zone 4) was determined to be the most economically viable zone for production based on the values of shale volume, porosity, and water saturation. The volume of hydrocarbon reserves in the BR-1 potential zone was calculated to be 182.741281 MBO in OOIP and 177.85122 BCF in OGIP. The BR-2 potential zone had an OOIP value of 1,197.534148 MBO and an OGIP of 1165.488764 BCF.